Cultivating the Early Literacy Experience Based on the Concepts of Tompkins and Hoskisson - Arifian, Florianus Dus (STKIP Santu Paulus Ruteng, 2016)
Early literacy experience is reguired for children in order that they can recognise written language. Yet, thecultivation of early literacy experience is a complex idea. Thus, there should be an explanatory study aboutit. Based onTompkins and Hoskisson, there are three main points related to the cultivation of early literacyexperience such as written language, reading, and writing. In the written language, children build theirperception about the functions of written language, texts, words, and alphabets based on the surroundingcontext. Meanwhile, reading and writing ability to children really requirea context, a process, an integrativeapproach, and a design of promotive literacy learning spaces.Keywords: emergent literacy, written language, context, process, integrative